Molecular Pathology and Diagnostics of Cancer - Coppola, Domenico; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
Molecular pathology is based on the emergence of new techniques that greatly enhance the diagnostic accuracy when facing with challenging differential diagnoses. In addition, new molecular techniques are entering the clinical arena for their value in predicting therapy response and tumor prognosis. This book provides a guide for the practicing pathologist and for both pathology residents and fellows during the daily sign-out of challenging cases. The book is organized by anatomical systems and provides a detailed description of molecular tests that may help in the diagnosis. Furthermore, a description of the current molecular tests required to identify patients for treatment is offered. The application of molecular pathology techniques to the clinical practice has already shown its usefulness and the number of such tests is growing exponentially as more molecular targets are discovered. Molecular Pathology and Diagnostics of Cancer will give practicing and training pathologists an up-to date resource to guide the correct management of pathology cases requiring molecular testing.
Preface -- Molecular Pathology and Diagnostics of Gliomas.-Molecular Pathology and Diagnostics of Thyroid and Parathyroid Malignancies -- Molecular Pathology and Diagnostics of Breast Cancer -- Molecular Pathology and Diagnostics of Non-Small Cell Lung Carcinoma -- Molecular Pathology and Diagnostics of Colorectal Cancer -- Molecular Pathology and Diagnostics in Esophago-Gastric Cancer -- Molecular-Genetic Testing in Hepatocellular Carcinoma and Its Premalignant Conditions -- Molecular Diagnostics of Pancreatic Cancer -- Molecular Pathology and Diagnostics of Prostate Cancer -- Molecular Diagnosis of Bladder and Kidney Cancer -- Molecular-Genetic Testing in Penile, Scrotal, and Testicular Cancer -- Molecular Pathology and Diagnostics of Gynecologic Malignancies -- Molecular Pathology of Bone and Soft Tissue Neoplasms and Potential Targets for Novel Therapy -- Molecular Pathology and Diagnostics of Pancreatic Endocrine Neoplasms -- Molecular Pathology and Diagnostics of Childhood Tumors -- Molecular Pathology and Diagnostics of Cutaneous Malignancy -- Molecular Diagnostics of Lymphoid Neoplasms -- Molecular Diagnostics of Myeloid Neoplasms.
Keywords: Medicine; Oncology; Pathology; Biomedicine; Cancer Research; Pathology; Biomedicine general